SPECIFIC ASPECTS OF THE OFFENSE OF LEAVING THE PLACE OF THE ACCIDENT - Alin-Sorin NICOLESCU; Luminiţa CRISTIU-NINU (Challenges of the Knowledge Society)
The legislator has adopted the respective texts of law to the new social realities once with the repeal of the criminal segment of GEO no. 195/2002 relating to the circulation on public roads, republished and the introduction of this one in the content of the New Criminal Code. The offence of leaving the place of the accident, actually found in the content of the provisions of art. 338 of Criminal Code is one of the eight offences against the safety on public roads. Knowing important modifications, the legal text may appear relatively ambiguous if we refer to the old indictment, meaning that certain factual situations remained outside the criminal law. We will analyse in this regard the obligations that arise to the driver in case of a traffic accident, bringing into question even the decriminalization of the prohibition of the consumption of alcohol after the road event. Furthermore, we will treat even aspects related to the causes of special no imputation that, on a closer analysis, can create problems of interpretation. Through the phrase “it does not constitute the offence of leaving the place of the accident when only material damages occurred after the accident”, the legislator has chosen to indict this offence even if the victim has evaluable lesions within 1-2 days of medical care, on condition that for the same fact, in the old regulation, 10 days were required or it was an oversight of the legislator that it is to be resolved at some point?